Both associative learning and speed–accuracy trade-off occur in the southern monarch butterfly when visiting flowers. Issue 1 (2nd January 2016) - Rodrigues, Daniela
Abstract : I examined the ability of the southern monarch butterfly ( Danaus erippus ) to associate colours with rewards, the consistency of individual learning abilities, and the potential trade-off between foraging speed and accuracy. To assess associative colour learning and individual learning abilities, I offered individual butterflies artificial flowers of two similarly preferred colours, orange and yellow. One colour of flower was rewarding (aqueous sucrose) and the other was non-rewarding (water); two groups of butterflies received reciprocal treatments. A second phase was employed to assess whether learning scores remained similar within individuals when aqueous sodium chloride (NaCl) was offered instead of water. In both phases, butterflies associated rewards with specific colours, regardless of the colour. No individual consistency in learning skills was detected. To examine whether southern monarchs trade off foraging speed with accuracy, butterflies were offered a flower array of three colours: one rewarding (orange) and two distractors (yellow and red). A second phase was employed to detect whether increasing the penalty of choosing an unrewarding colour by offering aqueous quinine hemisulphate instead of water increased attention levels. In both phases, butterflies chose rewarding flowers more often than unrewarding flowers. Butterflies that made correct choices varied greatly in their response times; the few individuals that made incorrect choices displayed exploratory flights of short duration, from 1 to 4 sec. Individuals that rapidly selected incorrect flowers in phase one were different from those that made incorrect choices in phase two. Butterflies vary in their cognitive abilities but do not show individual constancy in their learning skills or the speed at which they choose flowers. This study provides additional evidence that large-sized and long-lived butterfly species have good learning abilities. A pattern consistent with a speed–accuracy trade-off occurs when southern monarchs choose incorrect, unrewarding flowers.